OC-083 Aberrant expression of grem1 leads to ectopic stem cells capable of multilineage potential. (17th June 2017) - Biswas, S; Davis, H; Jansen, M; Treanor, D; Leedham, S
Abstract : Introduction: The stereotypical architecture of the intestinal wall is a strict organisational hierarchy with stem cells residing at the crypt base, progenitor cells just above proliferating rapidly in the transit amplifying compartment, and differentiated cells at the luminal surface. This is controlled by strictly regulated polarised gradients of Wnt and Bone Morphogenetic Proten (BMP) signalling. Our laboratory has shown that aberrant BMP signalling can promote stem cell activity away from the crypt base. Human hereditary mixed polyposis syndrome (HMPS) is an autosomal dominant condition, characterised morphologically by the development of ectopic crypt foci (ECF). HMPS is caused by a 40 kb duplication upstream of the BMP antagonist GREM1, which results in a compartmental expression switch of this secreted protein - from a restricted mesenchymal gradient to epithelial expression. A transgenic mouse ( Vil1-Grem1) modelling this switch developed an HMPS phenotype, with expansion of Lgr5- negative and Sox9- positive progenitors in ECF which proliferate and accumulate somatic mutations. We wished to determine whether these ECF contained stem cells, as evidenced by cellular renewal and multilineage differentiation. Method: A Vil1-Grem1; Sox9Cre ERT2 ; Rosa26 YFP model was created to allow recombination in Sox9 positive cells in both crypt base and ECF cells after tamoxifen injection and to mark their progeny. Serial images stained for YFP were scanned and 3D reconstruction performed to track the origins of clonal ribbons and allow full visualisation throughout polyps. Results: Lineage tracing revealed that as well as crypt basal cells, cells contained within intravillus ECF gave rise to clonal ribbons, indicative of stem cell function. These ribbons contained all the enteric cell lineages as confirmed on staining, suggesting ectopic stem cells are multipotential. Conclusion: Aberrant GREM1 expression causes cell fate disruption and accumulation of proliferating stem/progenitor cells within ectopic crypts. Ectopic crypt progenitor cells on the villus are capable of self-renewal and tissue-specific differentiation – properties suggestive of true stem cell potential. This evidence argues against an obligate unidirectional tissue organisational hierarchy in the intestine, and suggests that abnormally proliferating cells in the ectopic crypts may retain stem cell potential, yet are situated outside the protected environment of the crypt base stem cell niche. Consequently they may be more prone to mutation, due to atypical DNA damage response or due to altered mesenchymal microenvironment of the ectopic crypts. Reference: . Davis H, Irshad S, Bansal M, et al. Aberrant epithelial GREM1 expression initiates colonic tumorigenesis from cells outside the stem cell niche. Nat Med. 2015Jan;21(1):62–70 Disclosure of Interest: None Declared